Phytochemical Constituents and Pharmacological Activity of Malva parviflora plant: A Review - Naser, Estabraq H.; Mahdi, Lamyaa S.; Alasadi, Rawaa T. (Scientific Journal of Medical Research, 2022)
Malva parviflora L. is a perennial herbaceous plant from malvaceae family, largely distributed in areas with tropical, subtropical, and moderate climates of Asia, Africa, and Europe. M. parviflora contains glycosides, alkaloids, steroids, flavonoids, terpenes, saponin, and tannin in methanolic extract, flavonoids and alkaloid in petroleum ether extract, steroids, alkaloids, terpenes, flavonoids, and saponins in acetone extract, and steroids, flavonoids, saponins, tannins and terpenes in the water extract. In addition to other seven components incorporate ?- amyrin, ?-amyrin, a mixture of stigmasterol and ? sitosterol, cholesterol, campesterol, ?- sitosterol-O-?-D- glucoside and ergosterol in petroleum ether extract, tribuloside, a flavonoid glycoside, in ethyl acetate extract and ethyl vanillin in chloroform fraction. M. parviflora plant has important uses as a medicinal plant and an edible plant. High-Performance Liquid Chromatography (HPLC) analysis identified the major polyphenol components that were extracted at optimal conditions like ?-coumaric acid, naringenin, luteolin, cinnamic acid, and apigenin-7- glucoside. These results indicate that M. parviflora leaves extracts have DPPH radical scavenging activity and might be used as a natural source for bioactive compounds. Gas Chromatography-Mass Spectrometer (GC-MS) analysis of M. parviflora plant leaves showed the presence of several active components such as Pentadecanoic acid, 14-methyl ester, 10,13-octadecadienoic acid, methyl ester, Allantion, Trans-13-octadecenoic acid, methyl ester, 9,12 octadecadienoic acid (Z,Z) methyl ester, Methyl 10-trans, 12-cisoctadecadienoate, Hexasiloxane,1,1,3,3,5,5,7,7,9,9,11,11dodecamethyl, 4-hydroxy-3,5,5- trimethyl-4-(3- oxo-1- butenyl)-2-cyclohexenone,3,7,1,15-tetramethyl-2-hexadecenol, 6,10,14-trimethyl-2- pentadecanone, hexadecanoic acid, 9,12,15-octadecatrienoic acid methyl ester, and others. Malva parviflora L. has several pharmacological activities in various diseases. Leaves have benefits in swelling and wounds management. A lotion prepared from leaves is effective in the treatment of broken limbs and bruises. Leaves have benefits in swelling and wounds management. A lotion prepared from leaves is effective in the treatment of broken limbs and bruises. Malva parviflora has antioxidant, anti-carcinogenicity, anti-aging, anti-mutagenicity, antibacterial, anti-irritant, antidiabetic, neuroprotective, antifungal, anti-ulcerogenic, hepatoprotective, and analgesic.